2019
DOI: 10.1038/s41398-019-0388-7
|View full text |Cite
|
Sign up to set email alerts
|

S-nitrosylation of E3 ubiquitin-protein ligase RNF213 alters non-canonical Wnt/Ca+2 signaling in the P301S mouse model of tauopathy

Abstract: Mutations in the MAPT gene, which encodes the tau protein, are associated with several neurodegenerative diseases, including frontotemporal dementia (FTD), dementia with epilepsy, and other types of dementia. The missense mutation in the Mapt gene in the P301S mouse model of FTD results in impaired synaptic function and microgliosis at three months of age, which are the earliest manifestations of disease. Here, we examined changes in the S-nitrosoproteome in 2-month-old transgenic P301S mice in order to detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 68 publications
1
40
0
Order By: Relevance
“…It has been shown that NO regulates protein activities either through binding to transition metals of metalloproteins (metal nitrosylation) or covalent modification of cysteine ( S‐ nitrosylation) and tyrosine (tyrosine nitration) residues (Amal et al, ; Heinrich et al, ). In addition, NO can also function as an activator of soluble guanylate cyclase (sGC), a hemoprotein that has evolved to bind selectively to NO even in the presence of oxygen (Boon & Marletta, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that NO regulates protein activities either through binding to transition metals of metalloproteins (metal nitrosylation) or covalent modification of cysteine ( S‐ nitrosylation) and tyrosine (tyrosine nitration) residues (Amal et al, ; Heinrich et al, ). In addition, NO can also function as an activator of soluble guanylate cyclase (sGC), a hemoprotein that has evolved to bind selectively to NO even in the presence of oxygen (Boon & Marletta, ).…”
Section: Introductionmentioning
confidence: 99%
“…NO has a critical role in synaptic transmission in the brain [12] and plays a major role in signaling through the activation of GMP cyclase [12], effects on ion transporters [12], and S-nitrosylation (SNO) of peptides and proteins [13,14]. Numerous examples of neuropathologies exist that involve nitrosative stress (for review see [15,16]), including Alzheimer's [17], Parkinson's [18] and Huntington's diseases [19]. In addition, we have recently demonstrated the involvement of NO, SNO, and nitration in a mouse model of autism based on the SHANK3 human mutation [20].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the protocol applied in this study yields good comparability when compared to other studies on the synaptic proteome. Nevertheless, only a small overlap was found between the identified proteins and other studies on the SNO-proteome (Seneviratne et al 2016;Amal et al 2019). Yet, these studies analyzed whole-brain regions utilizing different models and enrichment strategies for nitrosylated peptides.…”
Section: Discussionmentioning
confidence: 75%
“…Studies carried out in NOS2 knockout mice have shown a correlation between NOS2, amyloid beta (Ab) deposition, and cognitive dysfunction in AD mouse models (Colton et al 2008;Kummer et al 2011). The SNO-proteome in cortex and hippocampus tissues is altered in both the CK-p25 mouse model of AD and the P301S mouse model of tauopathy (Seneviratne et al 2016;Amal et al 2019).…”
mentioning
confidence: 99%